Free Thyroxine Concentrations by Equilibrium Dialysis and Chemiluminescent Immunoassays in 13 Hypothyroid Dogs Positive for Thyroglobulin Antibody - Randolph, J.F. (J Vet Intern Med, 2015)
OBJECTIVE: To determine if concentrations of free thyroxine (FT4) measured by semi‐automated chemiluminescent immunoassay (CLIA) correspond to FT4 determined by equilibrium dialysis (ED) in hypothyroid dogs positive for thyroglobulin antibody (TGA). ANIMALS: Thirteen TGA‐positive dogs classified as hypothyroid based on subnormal FT4 concentrations by ED. METHODS: Qualitative assessment of canine TGA was performed using an enzyme‐linked immunosorbent assay. Serum total thyroxine and total triiodothyronine concentrations were measured by radioimmunoassay. Serum FT4 concentration was determined by ED, and also by semi‐automated CLIA for human FT4 (FT4h) and veterinary FT4 (FT4v). Canine thyroid stimulating hormone concentration was measured by semi‐automated CLIA. RESULTS: Each dog's comprehensive thyroid profile supported a diagnosis of hypothyroidism. For detection of hypothyroidism, sensitivities of CLIA for FT4h and FT4v were 62% (95% CI, 32–85%) and 75% (95% CI, 36–96%), respectively, compared to FT4 by ED. Five of 13 (38%) dogs had FT4h and 2 of 8 (25%) dogs had FT4v concentrations by CLIA that were increased or within the reference range. Percentage of false‐negative test results for FT4 by CLIA compared to ED was significantly (P < .0001 for FT4h and P < .001for FT4v) higher than the hypothesized false‐negative rate of 0%. CONCLUSIONS AND CLINICAL IMPORTANCE: Caution should be exercised in screening dogs for hypothyroidism using FT4 measured by CLIA alone. Some (25–38%) TGA‐positive hypothyroid dogs had FT4 concentrations determined by CLIA that did not support a diagnosis of hypothyroidism.